2015
DOI: 10.1080/00015458.2015.11681125
|View full text |Cite
|
Sign up to set email alerts
|

Making Surgical Care Safer: A Survey on the Implementation of the Checklist by Belgian Surgeons

Abstract: In this survey, the number of adverse event avoided thanks to the use of the SC demonstrates that SC -represents a simple strategy for addressing surgical patient safety in OT. Nevertheless, SC is still considered by many surgeons as an additional administrative burden and/or as just another gimmick. Further studies are needed to understand why some surgeons are still not willing to adapt to a changing safety culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…25 Checklists have been used successfully in improving healthcare quality and safety, such as the World Health Organization surgical safety checklist. 26 However, in studies of barriers to surgical safety checklist implementation in Australia, 26 in Belgium, 27 and in systematic reviews, 28 perceived disruption to workflow and conflicting priorities of stakeholders were barriers to embedding new processes into existing work routines. For a tool akin to a checklist that minimises workflow disruption, it is suggested that using a simple template proforma with headings for writing the diagnoses, treatment and follow‐up plan, in layperson language, may be a feasible strategy to achieve more effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…25 Checklists have been used successfully in improving healthcare quality and safety, such as the World Health Organization surgical safety checklist. 26 However, in studies of barriers to surgical safety checklist implementation in Australia, 26 in Belgium, 27 and in systematic reviews, 28 perceived disruption to workflow and conflicting priorities of stakeholders were barriers to embedding new processes into existing work routines. For a tool akin to a checklist that minimises workflow disruption, it is suggested that using a simple template proforma with headings for writing the diagnoses, treatment and follow‐up plan, in layperson language, may be a feasible strategy to achieve more effective communication.…”
Section: Discussionmentioning
confidence: 99%